2017
DOI: 10.1186/s12864-016-3394-7
|View full text |Cite
|
Sign up to set email alerts
|

Small RNA sequencing of cryopreserved semen from single bull revealed altered miRNAs and piRNAs expression between High- and Low-motile sperm populations

Abstract: BackgroundSmall RNAs present in bovine ejaculate can be linked to sperm abnormalities and fertility disorders. At present, quality parameters routinely used in semen evaluation are not fully reliable to predict bull fertility. In order to provide additional quality measurements for cryopreserved semen used for breeding, a method based on deep sequencing of sperm microRNA (miRNA) and Piwi-interacting RNA (piRNA) from individual bulls was developed.To validate our method, two populations of spermatozoa isolated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
130
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(150 citation statements)
references
References 69 publications
6
130
0
4
Order By: Relevance
“…In addition, sperm tsRNAs are subjected to numerous RNA modifications and edits that contribute to their stability (for review see [24]). Detailed studies of the sperm miRnome have also been undertaken in several species, including humans [25], mice [26,27], horses [28], pigs [29] and cattle [30,31]. Extensive variations in length and sequence composition of miR-NAs were detected by deep sequencing.…”
mentioning
confidence: 99%
“…In addition, sperm tsRNAs are subjected to numerous RNA modifications and edits that contribute to their stability (for review see [24]). Detailed studies of the sperm miRnome have also been undertaken in several species, including humans [25], mice [26,27], horses [28], pigs [29] and cattle [30,31]. Extensive variations in length and sequence composition of miR-NAs were detected by deep sequencing.…”
mentioning
confidence: 99%
“…In the present study, the miR-34a was found in a smaller quantity in a low-efficiency sample in IVEPs. Capra et al (2017) identified 83 miRNAs differentially expressed in the high-and low-motile sperm fractions separated by Precoll from four different bulls. Among these miRNAs were not the three miRNAs identified in the present work.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have investigated miRNAs through RNA sequencing of low and high motile cryopreserved spermatozoa. It was reported that numbers of miRNAs were expressed differentially in both the populations (Capra et al, ). Furthermore, the role of the particular miRNAs targeted genes has been found in the apoptosis, the integrity of the mitochondrial membrane and alteration in spermatogenesis, representing its role in fertility.…”
Section: Mirna and Spermatogenesismentioning
confidence: 99%